Magnetic Resonance Imaging (MRI): Principles, Applications, and Clinical Utility (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Magnetic Resonance Imaging (MRI) has become a cornerstone in diagnostic medicine, offering high-resolution images of soft tissues without the use of ionizing radiation. This paper reviews the principles of MRI, its applications across various medical fields, and discusses its clinical utility. We present data comparing MRI with other imaging modalities, analyze patient outcomes, and consider recent advancements in MRI technology.